2013
DOI: 10.1371/journal.pone.0070254
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Psychosocial Support for HIV Positive Adolescents in Harare, Zimbabwe

Abstract: BackgroundThere is a recognized gap in the evidence base relating to the nature and components of interventions to address the psycho-social needs of HIV positive young people. We used mixed methods research to strengthen a community support group intervention for HIV positive young people based in Harare, Zimbabwe.MethodsA quantitative questionnaire was administered to HIV positive Africaid support group attendees. Afterwards, qualitative data were collected from young people aged 15–18 through tape-recorded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
170
1
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(178 citation statements)
references
References 44 publications
4
170
1
1
Order By: Relevance
“…Stigmatization and discrimination may be one of the factors that these adolescents have experienced so that these could affect peer relationship and Prosocial behaviors [14,27]. In this study, adolescents with HIV infection were found to be at increased risks of having low self-esteem.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Stigmatization and discrimination may be one of the factors that these adolescents have experienced so that these could affect peer relationship and Prosocial behaviors [14,27]. In this study, adolescents with HIV infection were found to be at increased risks of having low self-esteem.…”
Section: Discussionmentioning
confidence: 64%
“…These may interfere with their independence and also their self-esteem. Psychosocial support should address ART adherence, future orientation, long-term consequences of risk behaviors, sexual and reproductive health and the coping ability of adolescents with HIV infection [7,14,28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This has stimulated interventions that can enhance positive parenting in HIV-positive caregivers in low-and middle-income countries. While evidence suggests that maternal illness is considered a risk for poor outcome in their children, where HIV-positive mothers were given the opportunity to enhance their capacity to deal with their illness and to strengthen parent-child relationship, the outcomes proved to beneit both the mental health of the caregiver and the child [33,39]. A few studies that emerged have started looking at the resilience in young children whose mothers are living with HIV in an atempt to improve developmental and psychosocial outcomes for both the HIV-infected mother and the child [17,33,39,47,58].…”
Section: Enhancing Resilience As a Protective Coping Mechanismmentioning
confidence: 99%
“…While evidence suggests that maternal illness is considered a risk for poor outcome in their children, where HIV-positive mothers were given the opportunity to enhance their capacity to deal with their illness and to strengthen parent-child relationship, the outcomes proved to beneit both the mental health of the caregiver and the child [33,39]. A few studies that emerged have started looking at the resilience in young children whose mothers are living with HIV in an atempt to improve developmental and psychosocial outcomes for both the HIV-infected mother and the child [17,33,39,47,58]. In the study with HIV-positive mothers from South Africa, there were also HIV-positive mothers who were able to express their own desires to live positively, for themselves and their children; they were also able to recognise how their own behaviour was afecting their children, and this had a positive impact on their ability to parent and communicate efectively with their children [58].…”
Section: Enhancing Resilience As a Protective Coping Mechanismmentioning
confidence: 99%